IDENTIFIKASI INTERAKSI OBAT PADA PERESEPAN PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS X - Khusna, Khotimatul (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2022)
Indonesia occupies the top ten countries with the highest population of people with Diabetes Mellitus in the world, which is ranked 5th with a range of 19.5 million people, and it is estimated that in 2045 it will increase to 28.6 million. Diabetes Mellitus is a chronic disease that is often accompanied by complications. This can lead to drug interactions. Drug interactions can affect the body's response to treatment. The purpose of this study was to determine the percentage of drug interactions on prescriptions received by patients with Type 2 Diabetes Mellitus at a health center in Surakarta. This research is a descriptive observational study. Data collection was carried out retrospectively through tracking records of drug use by patients with Diabetes Mellitus Type 2 at Puskesmas X. The sample in this study was all prescriptions for patients with Diabetes Mellitus Type 2 in April-December 2018. The results showed that the most prescribed antihyperglycemic drugs were 38, 89%, analgesics 16.20%, vitamins 14.2%, and antihypertensives 12.19%. The types of drugs that were most widely used in prescriptions were metformin at 18.98%, amlodipine at 11.57%, and paracetamol at 8.64%. The potential incidence of drug interactions is 62.5% of prescriptions. The conclusion of this study showed that the potential for pharmacokinetic drug interactions was 1.36%, the potential for pharmacodynamic drug interactions was 46.94%, and the incidence of unknown drug interactions was 51.70%.